PERBEDAAN KADAR KREATININ PLASMA PASIEN GGK DENGAN CAUSA DIABETES MELITUS DAN CAUSA HIPERTENSI DI RSUD dr.ISKAK TULUNGAGUNG - Pria Wahyu Romadhon Girianto (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2022)
Chronic Kidney Disease was the most common chronic disease in Indonesia. The effect was increased plasma creatinine levels, which causes the patient to get hemodialysis. The purpose of this research was to know the difference in plasma creatinine levels in Chronic Kidney Disease patients with ex-causa Diabetes Mellitus and ex-causa Hypertension. The research design was Comparative with Cross Sectional approach. The population was all Chronic Kidney Disease patients with ex-causa DM and ex-causa Hypertension, with samples of 28 patients with ex-causa DM and 28 patients with ex-causa Hypertension selected by purposive sampling. Laboratory tests were done to determine plasma creatinine levels. The research variables were plasma creatinine levels in Chronic Kidney Disease patients with ex-causa DM and ex-causa Hypertension. Data were collected by observation sheet. Statistical analysis using Mann-Whitney with α = 0,05, got p-value = 0,005. It can be concluded that there was a difference in plasma creatinine levels in Chronic Kidney Disease patients with ex-causa DM and ex-causa Hypertension in dr. Isaak Tulungagung General Hospital, where Chronic Kidney Disease patients with ex-causa DM have plasma creatinine levels higher than ex-causa Hypertension. The higher level of plasma creatinine in ex-causa DM patients caused more severe glomerular damage and resulted in a severely impaired filtration process.